Identification of new business models in micro and small enterprises in the energy sector - Ropuszyńska-Surma, Edyta; Węglarz, Magdalena (Contemporary organisation and management. Challenges and trends, 2020)
The initial identification of new business models in micro- and medium-sized energy enterprises is the aim of this paper. Based on the literature review, different definitions of business models were presented and a range of research conducted by other authors focusing on the business models in the energy sector was shortly described. The state of the art allows to identify a research gap suggesting that this type of companies has not yet been studied. Presented results of the research were addressed to micro- and medium-sized energy enterprises producing or delivering services connected with e.g. energy efficiency. The research was conducted with the use of a direct questionnaire on 30 respondents in November 2019. It was identified that the business models of these enterprises are classical. Two types of models were distinguished i.e. for companies whose key customers are households (B2C model) and business (B2B model).